2018
DOI: 10.1242/jcs.208017
|View full text |Cite
|
Sign up to set email alerts
|

Rheb localized on the Golgi membrane activates lysosome-localized mTORC1 at the Golgi–lysosome contact site

Abstract: In response to amino acid supply, mTORC1, a master regulator of cell growth, is recruited to the lysosome and activated by the small GTPase Rheb. However, the intracellular localization of Rheb is controversial. In this study, we showed that a significant portion of Rheb is localized on the Golgi but not on the lysosome. GFP-Rheb could activate mTORC1, even when forced to exclusively localize to the Golgi. Likewise, artificial recruitment of mTORC1 to the Golgi allowed its activation. Accordingly, the Golgi wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(75 citation statements)
references
References 64 publications
3
69
0
Order By: Relevance
“…Together with amino acid sensing signals from the cytosol, these cues converge on GATOR1/2 and lead to the recruitment of mTORC1 to the lysosome through interactions with a complex comprised of Ragulator and Rag GTPases . In addition, mitogenic signaling by phosphatidylinositol‐3‐kinase (PI3K) and Akt activate Rheb, which is required for activation of mTORC1 . As both mitogenic and metabolic arms are required for its activation, mTORC1 is selectively activated under conditions of nutrient sufficiency.…”
Section: Mtorc1 Coordinates Endocytic Membrane Traffic With Nutrient mentioning
confidence: 99%
“…Together with amino acid sensing signals from the cytosol, these cues converge on GATOR1/2 and lead to the recruitment of mTORC1 to the lysosome through interactions with a complex comprised of Ragulator and Rag GTPases . In addition, mitogenic signaling by phosphatidylinositol‐3‐kinase (PI3K) and Akt activate Rheb, which is required for activation of mTORC1 . As both mitogenic and metabolic arms are required for its activation, mTORC1 is selectively activated under conditions of nutrient sufficiency.…”
Section: Mtorc1 Coordinates Endocytic Membrane Traffic With Nutrient mentioning
confidence: 99%
“…As an alternative to the possibility that Rheb dynamically visits the surface of lysosomes in order to activate mTORC1, it was recently reported that Rheb instead resides on the Golgi and activates mTORC1 via contact sites between the Golgi and lysosomes (Hao et al, 2018). However, this study relied on assessing the ability of heavily over-expressed, Golgi-targeted Rheb, to hyper-activate mTORC1 signaling.…”
Section: Evidence In Favor Of Dynamic Interactions Between Rheb and Ementioning
confidence: 99%
“…Adding to the confusion concerning the relationship between Rheb localization and function, it has also recently been proposed that Rheb instead resides on either the ER or Golgi and activates mTORC1 via contact sites between these organelles and lysosomes (Hao et al, 2018;Walton et al, 2018). These recent observations are paralleled by some older studies that also reported enrichment of over-expressed Rheb at the endoplasmic reticulum (Buerger et al, 2006;Hanker et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…One of them is aligned with the recent realization and general trend in cell biology that material exchange and organelle biogenesis/remodeling occur at membrane contact sites involving different organelles [4]. Indeed, contact sites between the ER and mitochondria or the ER and the plasma membrane [5,6] have been reported as contributing to autophagosome biogenesis, whereas Golgi-lysosome contact sites may control signaling by mTOR, an upstream regulator of autophagy [7].…”
mentioning
confidence: 84%